Kerala Traditional Ayurvedic Practices in Children for Enhancing Immunity - A Systematic Review (International Journal of Ayurveda and Pharma Research, 2023)
Kerala is rich in its culture for the traditional Ayurveda practices in children from the time of birth onwards. These traditional practices are mainly immune boosters and also enhance overall nourishment and development in children. Commonly used traditional Ayurveda practices are Uramarunnu Prayoga, Prakara Yoga, Abhyanga, Rasanadi churna lepana, Snana etc. for enhancing immunity and providing overall development to children.  Uramarunnu is a baby care practice comprising of a group of drugs administered to the child in the form of paste in breast milk, after 28 days till 2 years of age. Prakara Yogas are immunomodulatory recipes and procedures to be adopted right from the day after delivery. Abhyanga provides nourishment, health, protection, emotional well-being and improves skin tone. All these can be used for enhancing immunity and preventing recurrent infections thereby helps in the maintenance of health and prevention of diseases. This mentions the importance of Kerala traditional Ayurvedic practices in the field of primary child health care. So, the present study aims to compile Kerala’s traditional Ayurvedic practices in children, by reviewing regional textbooks like Arogyakalpadruma, Vaidya Tarakam, Parambarya Balachikitsa etc., and also interviewing Ayurveda pediatrician through telephone.